Measuring cognitive and affective empathy across positive and negative emotions: psychometric properties and measurement invariance of the Perth Empathy Scale - Lashkari, Arezou; Brett, Jack D.; Abdolpour, Ghasem; Mazidi, Mahdi (Frontiers in Psychiatry, 2025)
IntroductionEmpathy, a complex and multidimensional construct essential for social functioning and mental health, has been extensively studied in both research and clinical settings. The Perth Empathy Scale (PES), a recently developed self-report measure, assesses cognitive and affective empathy across both positive and negative emotions and is based on the self-other model of empathy. This study aimed to evaluate the psychometric properties of the Persian version of the PES in large Iranian sample.MethodsA total of 868 Iranian adults participated in this study. Factorial validity was examined through Confirmatory Factor Analysis (CFA).Internal consistency and concurrent validity were assessed by examining correlations with established empathy measures, including the Interpersonal Reactivity Index (IRI) and the Questionnaire of Cognitive and Affective Empathy (QCAE), as well as the Perth Alexithymia Questionnaire (PAQ) and the Social Phobia Inventory (SPIN). Measurement invariance was also tested between Iranian and Australian samples.ResultsThe findings supported a three-factor model comprising cognitive empathy, negative affective empathy, and positive affective empathy. The Persian PES demonstrated structural validity, internal consistency, and concurrent validity, suggesting it is a reliable measure for empathy assessment across cultural contexts.DiscussionThis study provides empirical support for the validity of the Persian PES and contributes to the expanding body of research on empathy assessment. The results suggest that the PES can be effectively used in Persian- speaking populations.